Language engineering for lesser-studied language [ - Nirenburg, Sergei (NATO science for peace and security series D, Information and communication security, 2009)
Contains information about many core facets of modern computational-linguistic work. This book is suitable for people interested in learning about strategies that are best suited for developing computational-linguistic capabilities for lesser-studied languages - either 'from scratch' or using components developed for other languages